Safety and efficacy of stereotactic ablative brachytherapy as a salvage therapy for recurrent chest wall cancer: A retrospective, multicenter study - Huo, Bin; Ji, Zhe; He, Chuang; Yang, Wanying; Ma, Yanli; Huo, Xiaodong; Wang, Zhe; Zhao, Xinxin; Dai, Jinchao; Wang, Haitao; Chen, Guanglie; Wang, Ruoyu; et al. (Frontiers in Oncology, 2023)
Purpose: To investigate the safety and efficacy of stereotactic ablative brachytherapy (SABT) as a salvage therapy for recurrent chest wall cancer (rCWC) after external beam radiotherapy (EBRT) or surgery. Materials and Methods:This is a multicenter retrospective study of 130 patients (75 males, 55 females; median age 63 years) with rCWC who received SABT between November 2013 and October 2020, there were 97 cases of non-small-cell lung carcinoma, 24 cases of breast cancer and 9 cases of thymic cancer. Of the patients included, 102 patients previously received surgery and 58 patients received EBRT, with systemic treatment progressing after recurrence, and all were ineligible or rejected for salvage surgery and/or repeat EBRT. Results: During a median follow-up of 22 months (range, 4-70 months) , 59 patients died. The local control rates at 6 months, 12 months, 24 months and 36 months were 88.3% , 74.3% , 50.4% and 36.7% respectively. The 1-, 2-and 3-year survival rates were 85% , 56% and 42% , respectively.The median overall survival (OS) was 26 months(95% CI, 18.9-33.1 months). The pain relief rate was 81% , and the median to remission time was 10 days. Univariate and multivariate analysis showed that the tumor size and postoperative D90 were independent prognostic factors for local control. KPS score, tumor size and D90 were independent prognostic factors for survival . The complications were grade I/II skin reaction in 19 cases (14.6%) , No grade III or severer complications were found. Conclusion: SABT is safe and effective as a salvage therapy for rCWC after EBRT/surgery. For patients with KPS score greater than 80, prescribed dose greater than 130 Gy, and tumor size less than 4 cm may bring better results.